1991
DOI: 10.1111/j.1365-2559.1991.tb00873.x
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse sclerosing papillary carcinoma of the thyroid gland: immunohistochemical analysis of the local host immune response

Abstract: Surgical specimens from four patients with diffuse sclerosing papillary carcinoma of thyroid were examined by electronmicroscopy. In addition, immunohistochemical examination using a panel of monoclonal and polyclonal antibodies was carried out in order to investigate the expression of HLA-DR antigen, the presence of Langerhans' cells and the phenotypic characteristics of the inflammatory infiltrate. The ultrastructural study showed that the intraglandular dissemination, typical of this tumour, was due to mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…Dendritic cells, antigen‐presenting cells, are also observed in papillary thyroid carcinoma and the dense infiltrate suggests a more favorable prognosis (27). Chronic inflammatory reaction and abundant dendritic cells are characteristic of DSV (9, 10). We observed that dendritic cells were not only present in the stroma, but also between conventional carcinoma cells and within squamous metaplastic nests.…”
Section: Discussionmentioning
confidence: 99%
“…Dendritic cells, antigen‐presenting cells, are also observed in papillary thyroid carcinoma and the dense infiltrate suggests a more favorable prognosis (27). Chronic inflammatory reaction and abundant dendritic cells are characteristic of DSV (9, 10). We observed that dendritic cells were not only present in the stroma, but also between conventional carcinoma cells and within squamous metaplastic nests.…”
Section: Discussionmentioning
confidence: 99%
“…Several morphologic variants of PC have been described, some of them having a less favourable prognosis (e.g. tall‐cell PC, columnar cell PC, and diffuse sclerosing PC) than the ‘classical’ variant 17–29 . The oncocytic (oxyphilic, Hürthle cell) variant of thyroid PC represents a relatively unusual neoplasm, and its clinicopathological features and biological behaviour have not yet been fully characterized.…”
Section: Discussionmentioning
confidence: 99%
“…tall-cell PC, columnar cell PC, and diffuse sclerosing PC) than the 'classical' variant. [17][18][19][20][21][22][23][24][25][26][27][28][29] The oncocytic (oxyphilic, Hü rthle cell) variant of thyroid PC represents a relatively unusual neoplasm, and its clinicopathological features and biological behaviour have not yet been fully characterized. This tumour accounts for 1-11% of all cases of thyroid PC; the differences among reported series probably result from application of different classification criteria.…”
Section: Discussionmentioning
confidence: 99%
“…An association between thyroiditis and DSPC has been postulated. 5,[10][11][12] Therefore, the possibility of double pathology may have to be considered. Both our cases showed characteristic features of papillary carcinoma; therefore, the diagnosis was not difficult.…”
Section: Discussionmentioning
confidence: 99%